2014
DOI: 10.1111/bpa.12209
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory Pathology in Central Nervous System Demyelinating Diseases

Abstract: Olfactory dysfunction is common in multiple sclerosis (MS). Olfactory bulb and tract pathology in MS and other demyelinating diseases remain unexplored. A human autopsy cohort of pathologically confirmed cases encompassing the spectrum of demyelinating disease (MS; n = 17), neuromyelitis optica [(NMO); n = 3] and acute disseminated encephalomyelitis [(ADEM); n = 7] was compared to neuroinflammatory [herpes simplex virus encephalitis (HSE); n = 3], neurodegenerative [Alzheimer's disease (AD); n = 4] and non-neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
53
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(55 citation statements)
references
References 30 publications
(41 reference statements)
1
53
0
Order By: Relevance
“…The relation between olfactory-related structures and olfactory function was reported by Hummel et al and Lemasson et al, they thought the relation was grounded in adult neurogenesis and synaptogenesis [32,33]; trans-synaptic degeneration has been suggested as a contributor to chronic axon damage, associated with visual cortex atrophy in MS [34], while in NMO the hypothesis of neurogenesis and transsynaptical changes has not been clarified. However, a recent pathology study reported that inflammation and demyelination could present in olfactory structures [10]. Unfortunately, this study lacked olfactory assessment information.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…The relation between olfactory-related structures and olfactory function was reported by Hummel et al and Lemasson et al, they thought the relation was grounded in adult neurogenesis and synaptogenesis [32,33]; trans-synaptic degeneration has been suggested as a contributor to chronic axon damage, associated with visual cortex atrophy in MS [34], while in NMO the hypothesis of neurogenesis and transsynaptical changes has not been clarified. However, a recent pathology study reported that inflammation and demyelination could present in olfactory structures [10]. Unfortunately, this study lacked olfactory assessment information.…”
Section: Discussionmentioning
confidence: 91%
“…Olfactory dysfunction has been studied for many years and demyelination in olfactory-related structures were confirmed by pathologic studies in MS, while fewer cases and only chronic inactive lesions in olfactory bulb/tract demyelination were found in NMO; besides, aquaporin-4 was absent within NMO lesions compared to MS [10]. Different pathophysiological process between these two diseases might be the reason that there was a little higher olfactory deficit percentage in NMOSD than MS tested by Hawkes et al, Doty et al, Fleiner et al and so on.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Detailed investigation of such human specimens will expand our understanding of the neuropathogenesis of virus-induced encephalitis/encephalopathy and some neurodegenerative disorders in which early olfactory dysfunction and olfactory bulb pathology have much been described, such as Alzheimer's and Parkinson's diseases (Doorn et al, 2014). Furthermore, early and prominent olfactory dysfunction and pathology are common in demyelinating disorders including multiple sclerosis (DeLuca et al, 2015). Common respiratory viruses may be involved in the pathogenesis of these diseases (Majde, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Considering other brain regions not concerned to olfaction, the number of plaques did not have such relation. Olfactory bulb tract axonal loss was reported in 12 out of 17 MS patients 14 and related to the extension of demyelination in brain, especially in the inferior frontal cortex, although other areas beyond the orbitofrontal cortex are involved in the perception and processing of different odorants, as the insula, cerebellum, visual and cingulate cortex. Therefore, olfactory dysfunction could be an early indication of disease progression, and a marker of widespread disease in the brain.…”
mentioning
confidence: 99%